Mendekatkan Teknologi AI Pada Peserta Didik di Tingkat SLTA Untuk Melihat Tantangan dan Peluang Dunia Kerja - Sahulata, Reynoldus Andrias; Lontaan, Rolly Junius; Tombeng, Marchel Thimoty (Universitas Klabat, 2025)
Increasing efficiency in all areas ranging from business activities, health services, and handling of learning in education, by automating all repetitive activities that take time, requires effective handling. For this reason, Artificial Intelligence (AI) is needed to be able to assist in decision making through the analysis of large and complex data, as well as providing more accurate recommendations, thereby increasing productivity in the performance of automation on tasks that do not require creativity, thus allowing humans to focus on more complex tasks. Understanding the importance of strengthening AI knowledge since the time of Senior High School (SLTA), then provision is carried out in order to bring information system technology closer by utilizing basic AI from how to work, think and interact using AI which is formulated through practical guidance on using AI in creating web programming for basic applications as learning, for students at SMA Negeri 2 Bitung.